Influencing Factors to Use E-Hailing Transport for Food Delivery Service - Wan Mohamad Yusoff, Wan Azfizatul Az Zarah; Mohd Razip, Nuraisha Arissa; Ambak, Kamarudin; Ab Ghani, Ahmad Raqib; Putranto, Leksmono Suryo (International Journal of Sustainable Construction Engineering and Technology, 2023)
E-Hailing services are considered as on-demand vehicles that affect the efficiency of food delivery. This system improves the process of collecting and sending orders from customers in a short period of time. This study aims to determine the level of consumer acceptance or satisfaction with food delivery services using the e-Hailing system. The objective of this study is to identify the factors that influence the community to use e-Hailing food delivery services and to determine the most dominant factor in e-Hailing services according to Technology Acceptance Model (TAM). The location of the study is in the urban area and also semi-urban in the districts of Johor. A self-administrated online questionnaire was distributed among 258 respondents in the study area. Part of the questionnaire was constructed based on the TAM. Correlation and regression analysis were used in the analysis of this study. The results of this study show that the relationship between variables TAM (? = 0.443), perceived ease of use, and perceived usefulness are strongly correlated based on significant values (p < 0.001) showed the independent variable (Intention to Use) influenced the acceptance of user behaviour towards e-Hailing. Among the suggestions to increase consumers of food delivery services among e-Hailing users is to reduce delivery charges for nearby areas so that consumers can buy food at various stores. This can help other vendors and riders in this e-Hailing food delivery service.